Estudio de la simbología de las letras en la obra de Huon Le Roi: Li Abecés par ekivoche et li significations des letres - Ríos Guardiola, M. Gloria (Anales de Filología Francesa, 2009)
The 13th century writer from Picardy, Huon le Roi de Cambrai, presents the words of the alphabet in a composition of 446 verses. This work, which keeps a didactic, moralist, sometimes satiric, tone, allows us to go into the social and religious values of that time as well as the orthography of the period. We also launch the translation into Spanish of this poem written in Old French in order to permit the analysis of the letters as a system of symbols.